2008
DOI: 10.1517/14712598.8.7.895
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage perfusion fibrous bed bioreactor system for mass production of embryonic stem cells

Abstract: Background : Embryonic stem cells (ESCs) have unlimited proliferation potential and can differentiate into all cell and tissue types, and thus are ideal sources for cell therapy and drug screening. Current supplies of ESCs are limited by the available cell sources and inefficient culture methods that grow ESCs on surfaces coated with expensive extracellular matrix (ECM) proteins and in media containing expensive growth factors. Objective : To meet the demand for ESCs, it is necessary to develop an economical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 85 publications
(120 reference statements)
0
22
0
Order By: Relevance
“…Grayson et al [77] engineered anatomically shaped human bone grafts using human MSCs in a bioreactor with continuous perfusion and found that the bone matrix architecture and density correlated with the interstitial flow pattern and intensity. In addition, perfusion was found to give better pO2 control and more uniform cell distribution within 3-D scaffolds [78] , and facilitated long-term ESC culture to reach a high cell density [79] . MSC proliferation was enhanced in highly porous matrices at different flow rates (0.1-1.5 mL/min), and the higher flow rate of 1.5 mL/min upregulated osteogenic differentiation [80] .…”
Section: Flow Shear Forcementioning
confidence: 99%
“…Grayson et al [77] engineered anatomically shaped human bone grafts using human MSCs in a bioreactor with continuous perfusion and found that the bone matrix architecture and density correlated with the interstitial flow pattern and intensity. In addition, perfusion was found to give better pO2 control and more uniform cell distribution within 3-D scaffolds [78] , and facilitated long-term ESC culture to reach a high cell density [79] . MSC proliferation was enhanced in highly porous matrices at different flow rates (0.1-1.5 mL/min), and the higher flow rate of 1.5 mL/min upregulated osteogenic differentiation [80] .…”
Section: Flow Shear Forcementioning
confidence: 99%
“…If one T-75 culture flask supports the production of 2x10 6 cells in 2-3 days, production of 2.1x10 10 cells would require over 10,000 tissue culture flasks and up to 5 weeks of culture time (Ouyang & Yang, 2008). They also determined flask count and time estimates for Parkinson`s disease and diabetes.…”
Section: Adherent Culturementioning
confidence: 99%
“…A major roadblock that has been anticipated on the path to clinical implementation of ESC derived cellular therapies is the labour intensive and highly variable nature of small scale cultures. It has been estimated that as many as 26 billion human ESCs may be required as a starting point for treating one patient taking into account losses during culture, inefficient differentiation protocols, downstream processing and purification of mature cell types (Ouyang & Yang 2008). Based on current small scale culture techniques, thousands of static tissue culture flasks and several weeks to months of culture time would be required to generate this number of cells (Ouyang & Yang 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The convention in tissue culture is the growth of adherent or anchorage dependent cell types on the 2-dimensional (2D) surface of a tissue culture flask. Whilst currently accepted as the gold standard in a research setting, recent interest in tissue engineering applications has highlighted the fact that current 2D tissue culture environment is inadequate for the required scale-up in cell production 6 .…”
Section: Introductionmentioning
confidence: 99%